The Conflictual Construction of Sexual Identity in La insolación (BEOIBERISTIKA - Časopis za iberijske, latinoameričke i komparativne studije (ISSN: 2560-4163 Online), 2025)
La insolación of Carmen Laforet is the initial installment of the life trilogies featuring the protagonist Martín Soto. The character's adolescent development is chronicled between the ages of 14 and 17 in post-war Spain. During this process, the conflict between the naturally developing sexual identity and social norms intensifies, as the protagonist perceives sexual desire for his friend. This desire manifests itself in different ways: physical attraction inspired by the classical beauty of Greek and Roman mythology, Carlos's farewell kiss laden with erotic connotations, or the scene in which the two, naked, sleep together in Martín's bed. This behavior, considered completely inappropriate at the time between two young people of the same sex, arouses the ire of the father, who cruelly beats him and even considers sending him to a correctional facility. Thus, this article attempts to give a certain scientific gloss to this literary work and to reinterpret, within the historical and social context of Franco's regime, the theme of the construction of adolescent sexual identity. This theme, which even today is often approached in a simplistic manner, is examined here with the aim of deciphering the intimate links between the sexual norms and behaviors of the time, repressed desire, and its impact on Martín Soto's Bildungsroman.
Keywords: adolescence; sexual identity; La insolación; Francoism